Noisy Galvanic Stimulation Improves Roll-Tilt Vestibular Perception in Healthy Subjects - Keywan, Aram; Wuehr, Max; Pradhan, Cauchy; Jahn, Klaus (Frontiers in Neurology, 2018)
It has recently been demonstrated that noisy galvanic vestibular stimulation (nGVS) delivered as imperceptible white noise can improve balance control via the induction of stochastic resonance. However, it is unclear whether these balance improvements are accompanied by simultaneous enhancement to vestibular motion perception. In this study, 15 healthy subjects performed eight quiet-stance tasks on foam with eyes closed at eight different nGVS amplitudes ranging from 0mA (baseline) to 0.5mA. The nGVS amplitude that improved balance performance most compared to baseline was assigned as the optimal nGVS amplitude. For 13 out of 15 subjects an optimal nGVS could be determined, and therefore were included in the subsequent experimental procedures. The effect of nGVS delivered at the determined optimal intensity on vestibular perceptual thresholds was examined using direction-recognition tasks on a motion-platform, testing roll rotations at 0.2, 0.5 and 1.0Hz, both with active and sham nGVS stimulations. nGVS significantly reduced direction recognition thresholds compared to the sham condition at 0.5Hz and 1.0Hz, whilst no significant effect of nGVS was found at 0.2Hz. Interestingly, no correlation was found between nGVS-induced improvements in balance control and vestibular motion perception at 0.5 and 1Hz, which may suggest different mechanisms by which nGVS affects both modalities. For the first time, we show that nGVS can enhance roll vestibular motion perception. The outcomes of this study are likely to be relevant for the potential therapeutic use of nGVS in patients with balance problems.